PENGARUH KARAKTER INDIVIDU DAN PERSEPSI KEADILAN PADA KINERJA KARYAWAN (Studi Kasus Pada Hotel Di Kota Denpasar) - I Ketut Sudarsana (Jurnal Ilmiah Hospitality Management, 2017)
Improving the quality of human resources can be done through the utilization of various functions and personnel activities to ensure that they will be absorbed in the world of hospitality. Employee performance is influenced by various factors including individual characters and their perception of fairness in working. The purpose of this research is to examine the influence of individual characters and perceptions of fairness on employee performance as well as to identify the state of individual characters and the perception of fairness to employee performance at the hotel in Denpasar. The results showed that individual character, and perception of fairness simultaneously have a significant effect on the performance of Hotel employees in Denpasar. Furthermore, partially individual characters, and the perception of fairness affect the performance of hotel employees in Denpasar. Because the perception of fairness has a dominant effect on employee performance, the management is expected to give sufficient attention to the amount of rewards received by the employee so that they are always motivated in doing every job that has become their duty. Giving authority in decisions, responses and good attention from superiors and the existence of a system of fair division of tasks should be maintained by the management in order to maintain the company performance.